The impact of COVID-19 on foot and ankle surgery in a major trauma centre. (March 2021) - Stringer, Howard; Molloy, Andrew; Craven, Joanne; Moorehead, John; Santini, Alasdair; Mason, Lyndon
Highlights: COVID-19 has significantly impacted on the foot and ankle trauma activity in our department. The triaging and rationing of services were mitigated by the overall reduction in trauma cases presenting to the department. There were no COVID-19 positive cases in our cohort. There was a change in normal practice in 31% of fractures. Malleolar fractures were the most significantly affected by rationing of service. Abstract: Introduction and aims: COVID-19 has had a significant impact on orthopaedic surgery globally. This paper aims to evaluate the impact of COVID-19 on foot and ankle trauma in a major trauma centre. Methods: A retrospective observational study of prospectively collected data was performed. All foot and ankle trauma patients over a 33 week period (1st December 2019–16th July 2020) were analysed. All patients with trauma classified by the AO/OTA as occurring at locations 43 and 81–88 were included. Results: Over the 33 weeks analysed, there was a total of 1661 trauma cases performed; of these, only 230 (13.85%) were foot and ankle trauma cases. As percentage of cases during each period of lockdown, foot and ankle made up 15.20% (147 out of 967) pre-lockdown, 8.81% (17 out of 193) during lockdown and 13.17% (66 out of 501) post lockdown. This difference was statistically significant (p < .001). The most significant change in trauma management was the treatment of malleolar fractures. Further analysis showed that during the lockdown period 29 foot and ankle fractures were treated the same and 13 were treated differently, (i.e. 31% of fractures were treated conservatively, when the consultants preferred practice would have been surgical intervention). Of the 13 patients, 3 have had surgical management since lockdown has been eased. Conclusion: It is evident that the trauma case activity within foot and ankle was significantly reduced during the COVID-19 period. The consequences of change in management were mitigated due to a reduction in case load.